2004
DOI: 10.1207/s15516709cog2804_5
|View full text |Cite
|
Sign up to set email alerts
|

Moving words: dynamic representations in language comprehension*

Abstract: Eighty-two participants listened to sentences and then judged whether two sequentially presented visual objects were the same. On critical trials, participants heard a sentence describe the motion of a ball toward or away from the observer (e.g., "The pitcher hurled the softball to you"). Seven hundred and fifty milliseconds after the offset of the sentence, a picture of an object was presented for 500 ms, followed by another picture. On critical trials, the two pictures depicted the kind of ball mentioned in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(127 citation statements)
references
References 24 publications
12
110
1
4
Order By: Relevance
“…For example, Zwaan and Yaxley (2003) found that spatial iconicity affects semantic relatedness judgments (e.g., people were faster to judge BASEMENT and ATTIC as semantically related words when they saw ATTIC above BASEMENT than when they saw BASEMENT above ATTIC). Zwaan, Madden, Yaxley, and Aveyard (2004) have also shown effects of language on perceptual judgments. For example, participants were shown pictures of objects and asked to judge whether the second object was the same as the first.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Zwaan and Yaxley (2003) found that spatial iconicity affects semantic relatedness judgments (e.g., people were faster to judge BASEMENT and ATTIC as semantically related words when they saw ATTIC above BASEMENT than when they saw BASEMENT above ATTIC). Zwaan, Madden, Yaxley, and Aveyard (2004) have also shown effects of language on perceptual judgments. For example, participants were shown pictures of objects and asked to judge whether the second object was the same as the first.…”
Section: Discussionmentioning
confidence: 95%
“…According to this view, we activate positional and orientational information when presented with linguistic stimuli (e.g., Zwaan et al, 2004;Zwaan & Yaxley, 2003). In the case of spatial prepositions, this information might correspond to core members of the spatial prepositional categories, leading to the observed shift in picture representation toward the center of the prepositional category when a spatial preposition has been processed during encoding.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating between the umbrellas is thus dependent on one's representation of the sensorimotor characteristics associated with the object. This is something a propositional representation of text comprehension, in which the umbrella might be represented as a list of features or a node in a propositional network that would not differ according to location, cannot easily account for (Zwaan, Madden, Yaxley, & Aveyard, 2004).…”
Section: Present Experimentsmentioning
confidence: 99%
“…A number of findings suggest that people do spontaneously engage in imagery during language comprehension, and that processing language affects performance in subsequent perceptual tasks (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%